Website Optimization of Digital Literacy Based Media Services - Eman Wahyudi Kasim (IAIN AMBON, 2021)
Abstract: The development of science and technology today cannot be separated from the progress of internet services that are getting better and more comprehensive. This must be used optimally to encourage the creation of a superior and productive generation such as supporting the national literacy movement in the campus environment through community service activities. Service activities in the form of optimizing website-based student literacy media are expected to be a solution to support the literacy movement in the IAIN Ambon campus, especially in the Madrasah Ibtidaiyah Teacher Education study program. In addition, the existence of website-based literacy media can be a place to actualize students' ideas or ideas in a quality work. Keywords: Media,Literacy,Website